Chronic Obstructive Pulmonary Disease (COPD) Screening is Still a Challenge in Pakistan - Anam Rehman; Hamid Shafiq; Shireen Jawed; Fakiha Behram (Aziz Fatimah Medical and Dental College, 2019)
Background: Chronic obstructive lung disease (COPD) is a highly preventable disease with smoking as most recognizable risk factor globally. COPD remains undiagnosed worldwide due to unavailability of gold standard spirometry. Technical difficulties in this procedure, faced by patient result in over and under diagnosis of this prevalent disease. Objective of this study was to screen the undiagnosed air way obstruction which reflects the COPD among the smokers and nonsmokers. PEFR was used for assessment, as it is simple, reliable and easily available way at most of the health care centers. Methodology: A cross sectional study was conducted from May 2018 to Dec 2018 at private medical institute and private hospital in Faisalabad. It comprised of 200 males (smokers and nonsmokers) who had no previous history of diagnosis of COPD. Relevant information related to smoking including pack years and medical history specially related to COPD was inquired on structured questionnaire. Air way obstruction was assessed by PEFR using vitalograph compact. Data was analyzed by SPSS 21 version. Continuous variables are presented as mean and standard deviation (SD) and compared by Independent t-test among study groups. Categorical variables are expressed as proportions and compared by X2 test. P value ? 0.05 was considered significant. Results: Results are showing that 91.56% of the studied smokers have air way obstruction based on yellow and red zones of PEFR. Out of total COPD smokers 62.7% were in yellow zone and 28.9% were in red zone. Only 29.1% of nonsmokers have PEFR values within yellow. None of nonsmoker was in red zone (P value 0.001*). PEFR was significantly lower in smokers in comparison to nonsmokers (P value 0.003*). 95.5% of Subjects in red zone were symptomatic, while only 51.2% of subjects in yellow zone were symptomatic considering mild to severe air flow obstruction. Conclusion: Smokers and nonsmokers have undiagnosed airway obstruction with symptoms reflecting COPD but greater proportion of smoker were involved. PEFR was lower in smokers as compared to nonsmokers.